Szechwan Lovage Rhizome Extract Improves Renal Function and Alleviates Inflammatory Responses in Pyelonephritis Rats Infected with Escherichia Coli via IL-6/STAT3 Axis: Szechwan Lovage Rhizome Extract Effects on RF and IRs - Ji, Juan; Bi, Zhaoyu; Tian, Ling; Hou, Shufeng; Zhang, Qian; Li, Song (Cellular and Molecular Biology, 2023)
The objective of this study was to probe the effect and mechanism of Szechwan Lovage Rhizome (Chuanxiong, CX) extract on renal function (RF) and inflammatory responses (IRs) in acute pyelonephritis (APN) rats infected with Escherichia coli (E. coli). Fifteen SD rats were randomized to intervention, model and control groups. Rats in the control were fed normally without treatment, rats in the APN model were infected with E. coli, and rats in the intervention group were intragastrically administered CX extract after infection with E. coli. HE staining detected pathological changes in the kidney tissues in rats. Levels of renal function indexes and inflammatory factors (IFs) were measured by ELISA and an automatic biochemical analyzer. Besides, levels of IL-6/signal transducer and activator of transcription 3 (STAT3) pathway-related genes in rat kidney tissue were detected by qRT-PCR and western blot. the experimental results showed that IL-1β, IL-8, TNF-α and RF levels were the highest in the model group and the lowest in the control group, with those of the intervention group in between (P<0.05). Besides, the IL-6/STAT3 axis was markedly activated in the model group but inhibited in the intervention group (P<0.05). Subsequently, activated IL-6/STAT3 signal promoted IFs (IL-1β, IL-8 and TNF-α) and RF (BUN, Scr, β2-MG and UA), but this effect was offset after CX treatment (P<0.05). In conclusion, CX extract could improve RF and inhibit IRs of APN rats infected with E. coli by inhibiting the IL-6/STAT3 axis, which may be a new choice for APN treatment in the future.